Not following COVID-19 Treatment and Protocol Leading to Death: Not a Case of Medical Negligence: Chhattisgarh High Court (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
Negligence is the breach of a duty caused by omission to do something which a reasonable man guided by those considerations which ordinarily regulate the conduct of human affairs would do, or doing something which a prudent and reasonable man would not do. The definition of negligence as given in Law of Torts, Ratanlal & Dhirajlal (edited by Justice G.P. Singh), referred to hereinabove, holds good. The essential components of negligence are three: ‘duty’, ‘breach’ and ‘resulting damage’. A case has been filed before Chhattisgarh High Court with two-fold prayer; one is that the hospital is responsible for the negligent treatment and another one that the hospital did not follow the covid protocol norms in handling the dead body therefore liable to be prosecuted [Para 1]. High Court observed that the primary allegation of the petitioner that there has been a negligence in the treatment and wrong injection i.e. Remdesivir Injection was administered to the mother of the petitioner by which her health condition was deteriorated. With respect to the medical negligence and criminal case whether under the circumstances Remdesivir Injection was necessary or not, it cannot be tested by the Court [Para 5]. High Court further observed that with respect to the second aspect of the complaint that the dead body was not handled according to the covid protocol guidelines issued by the Central and State Government, this Court in exercise of power under Article 226 of the Constitution cannot go into the roving enquiry; in as much as, the nature of complaint as has been stated that the dead body was handed over without any zipped body bag is a matter of enquiry. Chhattisgarh High Court, therefore, refrained itself to go into the exercise of investigation. High Court added that serving certain problem requires multi-pronged approach and they would persist if viewed through narrow lens and the petitioner therefore cannot accept ill-conceived exercise by this court to substantiate the fact and allegation.
Keywords: COVID-19 protocol; Death; Complication; RTPCR report; Medical negligence